DAMPAK PERKEBUNAN KELAPA SAWIT PT. KRESNA DUTA AGROINDO TERHADAP SOSIAL EKONOMI MASYARAKAT DI DESA TANAH ABANG KECAMATAN PAMENANG KABUPATEN MERANGIN PROVINSI JAMBI - Fajar Susilo; Teguh Kismantoroadji; Siti Hamidah (Jurnal Dinamika Sosial Ekonomi, 2015)
This study aimed to analyze the social condition (education and health) and to analyze the economic condition (income and income gap) of the community around the company, with the presence of oil palm plantation company PT. Kresna Duta Agroindo (PT. KDA) at Tanah Abang Village, Pamenang Sub-District, Merangin Regency, Jambi Province. The basic method in this study was descriptive and the application used survey technique. With purposive sampling, a village was selected, Tanah Abang Village because it's the closest village to Kresna Duta Agroindo company (PT. KDA) and is the largest village and has the biggest population of farmer around the company. Total sample in this study was 60 respondents. The result of the study showed that the presence of PT. Kresna Duta Agroinda increased the quality of education and health and increased the income of the community, however, the high income leads to inequality. Keywords theimpact, oil palm plantation, community, social, economy.